The Genetic Diversity of Endophytic and Phyllosphere Bacteria from Several Indonesian Herbal Plants - Soka, Yogiara Susan; Magdalena, Stella; Rachelia, Devi (Makara Journal of Science, 2012)
Herbal plants have been believed by Indonesians to be an alternative medicine to treat illnesses. The bioactive compounds in the plant can be derived from secondary metabolites or from endophytic and phyllosphere bacteria which coexist within medicinal plants. A total of 18 endophytic bacteria and 32 phyllosphere bacteria were isolated from the herbal plants of Citrus sp., Pluchea indica, Curcuma longa, Nothopanax scuttelarium, Piper crocatum, and Andrographis paniculata. About 72% of endophytic bacteria isolates have proteolytic activity and about 11% have lipolytic activity. On the other hand, about 59% of phyllosphere bacteria isolates have proteolytic activity and about 19% have lipolytic activity. Phylogenetic diversity analysis was conducted by using the amplified ribosomal DNA restriction analysis (ARDRA) method and the sequence of 16S rDNA was digested with endonuclease restriction enzymes: MspI, RsaI, and Sau961. The diversity of endophytic and phyllosphere bacterium from the samples of herbal plants was high. Bacteria isolated from the same herbal plant does not always have a close genetic relationship except for the bacteria isolated from the P. indica plant which showed a close genetic relationship with each other